Controle biológico de Alternaria alternata, agente causal da mancha marrom de alternaria, por Bacillus SPP - Souza, Ariane do Carmo (2018)
The alternaria brown spot, caused by Alternaria alternata f sp. citri, causes large economic damages in tangor Murcott (Citrus sinensis Osbeck x Citrus reticulata [L.] Blanco). Its control is carried out through the spraying of agrochemicals, implying up to 15 pulverizations per year, which causes an increase in the production costs of the cultures and damages to the environment. As an alternative, the use of microorganisms, in particular Bacillus spp., has been used to diseases’ control. Therefore, the aim of this work was to evaluate the viability of Bacillus spp in in vitro and in vivo conditions. The methodologies were based on the interactions between biological control agents (Bacillus spp.) and the phytopathogen A. alternata, evaluated by the paired culture technique, by the production of volatile, thermostable and cell-free metabolites by different Bacillus spp. isolates. The molecular identification of the isolates tested and the efficacy of bacterial isolates were evaluated in leaves and plants under greenhouse conditions. The results showed that most of the isolates affected the development of phytopathogen and produced some types of metabolite, being antibiosis one of the probable mechanisms of action of the bacterium. The isolates ACB-01, ACB-07, ACB-08, ACB-18 and ACB-57 presented potential for disease control of A. alternata.